Cover Image. Issue 8 (2nd August 2021) - Unknown
Abstract : Top Row, L‐R: Primary myoblast cultures from WT and Braf L597V mutant (LV) mice, grown in low serum Differentiation Media (DM) at 48 hours. Bottom Row, L‐R: Primary WT and LV myoblasts with 1 μM MEK inhibitor at 48 hours in DM. Immunofluorescent labeling of MyHC with MF20 antibody was used to distinguish between differentiated (MyHC positive, green) and undifferentiated MyHC negative cells. Nuclei were counter‐stained with DAPI (blue). Shown are merged images at 10x magnification. From: Ras/MAPK dysregulation in development causes a skeletal myopathy in an activating BrafL597V mouse model for cardio‐facio‐cutaneous syndrome ; Yoshiko Maeda, William E. Tidyman, Bradley P. Ander, Catrin A. Pritchard and Katherine A. Rauen. Dev Dyn 250:8; pp. 1074–1095.